Pembuatan Prototipe Aplikasi Distribusi Pangan Berbasis Sistem Informasi Geografis (SIG) - Henny Medyawati; Budi Setiawan; Ega Hegarini; Imam Ahmad Trinugroho (Jurnal Nasional Teknologi Terapan (JNTT), 2018)
Food distribution and supply chain are the main problems to achieve food security in Indonesia. Geographical gaps, poor transportation systems and social differences in Indonesia induce a high complexity challenges to implement a perfect distribution system that can suitable with Indonesia characteristic. The purpose of this research is building a prototype for food distribution application using geographical information system (GIS) that can be implemented in Indonesia. GIS can visualize the entire data layer into a map which is easier to analyze. Indonesia consists of 34 provinces that spread over many island, each has specific geographical profile and transportation problems. This can be used as data layers with other instruments which related with food distribution in Indonesia. Building a food distribution application prototype is part of developing food distribution system which produce prototype of the system. Prototyping approach is being used to evaluate the designing result of GIS with analyzing features for food distribution in Indonesia. Final result for this research is an application that can be implemented into food distribution system that can create a stable food security in Indonesia, for all of the provinces.